2015
DOI: 10.3389/fpsyg.2015.01556
|View full text |Cite
|
Sign up to set email alerts
|

Modality use in joint attention between hearing parents and deaf children

Abstract: The present study examined differences in modality use during episodes of joint attention between hearing parent-hearing child dyads and hearing parent-deaf child dyads. Hearing children were age-matched to deaf children. Dyads were video recorded in a free play session with analyses focused on uni- and multimodality use during joint attention episodes. Results revealed that adults in hearing parent-deaf child dyads spent a significantly greater proportion of time interacting with their children using multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 26 publications
5
37
0
1
Order By: Relevance
“…Vocal imitation is considered to be a part of turn-taking structures in dyadic communicative exchanges (Hallgen, 2012;Papousek & Papousek, 1989;Pawlby, 1977). Recent studies showed there were fewer and shorter turn-taking sequences (Depowski, Abaya, Oghalai, & Bortfeld, 2015;Tait, De Raeve, & Nikolopoulos, 2007) and a greater proportion of speech overlap in dyadic vocal interactions with HI as compared to NH infants (Fagan, Bergeson, & Morris, 2014). Thus, our results agree with evidence from previous studies confirming the effect on infant hearing loss on characteristics of mother-infant vocal interactions (Fagan et al, 2014;Tait et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Vocal imitation is considered to be a part of turn-taking structures in dyadic communicative exchanges (Hallgen, 2012;Papousek & Papousek, 1989;Pawlby, 1977). Recent studies showed there were fewer and shorter turn-taking sequences (Depowski, Abaya, Oghalai, & Bortfeld, 2015;Tait, De Raeve, & Nikolopoulos, 2007) and a greater proportion of speech overlap in dyadic vocal interactions with HI as compared to NH infants (Fagan, Bergeson, & Morris, 2014). Thus, our results agree with evidence from previous studies confirming the effect on infant hearing loss on characteristics of mother-infant vocal interactions (Fagan et al, 2014;Tait et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Even after cochlear implantation or fitting with hearing aids, the signals they receive are still often suboptimal and can affect not only their sound processing but also their language learning (Bergeson, Houston, & Miyamoto, ; Houston, Stewart, Moberly, Hollich, & Miyamoto, ). The (lack of) auditory experiences they have from early life likely creates different patterns and trajectories when they interact with their hearing parents, who mostly rely on auditory/verbal mode of communication (Bortfeld & Oghalai, ; Depowski et al, ). These children did not only have a different start point from their hearing peers, they also have a different history in interacting with their parents which may have cascading effects on their social interaction with their parents.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies focusing on intentionality or mutual awareness aspects of joint attention have shown that, compared to their hearing peers, children with hearing loss were less successful in initiating and responding to their parents' attentional bids, and therefore, less likely to achieve joint attentional states with their parents (Bortfeld & Oghalai, ; Depowski et al, ). Using a leaner definition and focusing on the micro‐level gaze data, our study showed that children with hearing loss had similar coordinated attention patterns as their hearing peers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations